THE PROFESSIONAL DIAGNOSTICS AND EMPLOYMENT OF STUDENTS WITH DISABILITIES - S. Grishaeva; A. Mitrofanova; E. Mitrofanova (Вестник университета, 2018)
The authors conducted a research of employment problem of graduates with disabilities. Specifics justification of professional diagnostics of students with disabilities has been substantiated. Types and methods of professional diagnostics, the basic rules and difficulties of performing professional diagnostics of persons with disabilities have been defined. The main directions of assistance to employment of students with disabilities have been offered. The technique of regional labor market monitoring including the solution of such tasks as a research of regional labor market and assessment of a jobs offers for persons with disabilities have been developed and approved; formation of a vacancies databank for graduates with disabilities; development of social partnership for the purpose of employment of graduates with disabilities.